Dating the Orosirian orogen-parallel shear zones in the western Khondalite Belt, North China Craton: new constraints from monazite, titanite and apatite U-Pb ages - Qiao, Hengzhong; Liu, Miao; Dai, Chencheng; Wu, Shangjing (Frontiers in Earth Science, 2025)
A series of NE-to E-trending ductile shear zones are widely distributed in the Khondalite Belt, a Paleoproterozoic collisional orogen in the North China Craton. Available geochronological investigations have been mainly focused on metamorphic and magmatic events in the Khondalite Belt, but the deformation age of ductile shear zones remains poorly constrained. In this paper, we conducted field-based structural and U-Pb geochronological studies on the Helanshan ductile shear zones (HDSZ) and Qianlishan ductile shear zones (QDSZ) in the western Khondalite Belt. The results revealed that four pre-kinematic intrusions were reworked by the shear zones and yielded monazite U-Pb ages of 1954 ± 3 Ma, 1942 ± 10 Ma, 1925 ± 5 Ma and 1918 ± 4 Ma, suggesting that the HDSZ and QDSZ probably appeared at some time after ∼1918 Ma. In the HDSZ, a granitic mylonite gave titanite and apatite U-Pb ages of 1897 ± 32 Ma and 1866 ± 47 Ma. Similar apatite U-Pb ages of 1860 ± 78 Ma and 1823 ± 50 Ma were also reported from another two mylonitized rocks. Comparably, three mylonites from the QDSZ displayed apatite ages of 1878 ± 39 Ma, 1805 ± 16 Ma and 1801 ± 10 Ma. Notably, these titanite and apatite U-Pb ages of 1897–1801 Ma are in good agreement with those of 1904–1823 Ma obtained from zircon overgrowth rims in mylonites. We regard that the above-stated U-Pb ages of 1904–1801 Ma together recorded the timing of the shear zone activity in the western Khondalite Belt. Combined with previous structural and geochronological data, we propose that the post-collisional orogen-parallel ductile shear zones in the Khondalite Belt have developed at ca. 1.90–1.80 Ga.